Smoking Habits of Relatives of Patients with Cancer: Cancer Diagnosis in the Family is an Important Teachable Moment for Smoking Cessation - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2013)
Background: In this study we aimed to determine the rate and habitual patterns of smoking, intentions of cessation, dependence levels and sociodemographic characteristics of relatives of patients with a diagnosis of cancer. Materials and Methods: This study was designed by the Turkish Oncology Group, Epidemiology and Prevention Subgroup. The relatives of cancer patients were asked to fill a questionnaire and Fagerstrom test of nicotine dependence. Results: The median ages of those with lower and higher Fagerstrom scores were 40 years and 42 years, respectively. We found no evidence of variation between the two groups for the remaining sociodemographic variables, including the subject's medical status, gender, living in the same house with the patient, their educational status, their family income, closeness to their cancer patients or spending time with them or getting any help or wanting to get some help. Only 2% of the subjects started smoking after cancer was diagnosed in their loved ones and almost 20% of subjects had quit smoking during the previous year. Conclusions: The Fagerstrom score is helpful in determining who would be the most likely to benefit from a cigarette smoking cessation program. Identification of these people with proper screening methods might help us to pinpoint who would benefit most from these programs.
Keywords: Cancer; smoking habits; fagerstrom score; relatives of cancer patients; QUIT SMOKING; MOTIVATION; PREDICTORS; DISTRESS